Drug therapy and sexual disorders - Vitale, Ann E. (Psychiatric disorders, 2004)
Describes the characteristics and various treatments, such as drugs, psychoanalysis, and behavior modification, of sexual disorders, including gender identity disorders, paraphilias, and sexual dysfunctions.